2015
DOI: 10.1161/jaha.115.002379
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Renal Artery Stenosis Prevalence and Correlations in Acute Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Interventions: Data From Nonrandomized Single‐Center Study (REN‐ACS)—A Single Center, Prospective, Observational Study

Abstract: BackgroundWe are the first to evaluate the prevalence of renal artery stenosis (RAS) in consecutive patients with acute myocardial infarction (AMI) referred for primary percutaneous coronary intervention from a single tertiary center. As a novelty, we assessed hydration and metabolic status and measured arterial stiffness. We elaborated a predicting model for RAS in AMI.Methods and ResultsOne hundred and eighty‐one patients with AMI underwent concomitantly primary percutaneous coronary intervention and renal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…Evaluation using the difference of the renal RIs between the left and right kidneys is hampered in the case of a single kidney where the contralateral kidney is not available for comparison, and (in particular) in bilateral RAS where RAS might be not considered, since examiners are focused on a RI‐difference between the 2 kidneys. Several angiographic studies suggest that RAS occurs bilaterally in about 20%‐25% of the cases . In an examination on pediatric patients, bilateral RAS has been observed even in 47% .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation using the difference of the renal RIs between the left and right kidneys is hampered in the case of a single kidney where the contralateral kidney is not available for comparison, and (in particular) in bilateral RAS where RAS might be not considered, since examiners are focused on a RI‐difference between the 2 kidneys. Several angiographic studies suggest that RAS occurs bilaterally in about 20%‐25% of the cases . In an examination on pediatric patients, bilateral RAS has been observed even in 47% .…”
Section: Discussionmentioning
confidence: 99%
“…Several angiographic studies suggest that RAS occurs bilaterally in about 20%-25% of the cases. 25,[27][28][29] In an examination on pediatric patients, bilateral RAS has been observed even in 47%. 30 In this study, we found bilateral RAS in 25%, which is well in the range reported by others.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Moreover, MetS may impose vascular remodeling and accelerate development of atherosclerotic lesions. Renal artery stenosis, detected in 16% patients with cardiovascular events,[31] further decreases blood supply to the kidney and exacerbates renal damage. Indeed, in post-stenotic swine kidneys, MetS precipitates or magnifies loss of microvessels,[15] thereby aggravating tissue injury.…”
Section: Microvascular Remodelingmentioning
confidence: 99%
“…In a previous study, we also found that the unilateral and bilateral RAS rates were 17 and 6.2% respectively [50]. Some authors suggested that coronary and renal artery angiography should be performed simultaneously in patients with myocardial infarction [54].…”
Section: Discussionmentioning
confidence: 70%